2021
DOI: 10.31729/jnma.5698
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki Disease- Management Strategies Given Symptoms Overlap to COVID-19: A Review

Abstract: Kawasaki disease is an acute, self-limiting vasculitis in children. Early treatment is necessary to prevent cardiovascular complications. The acute phase of Kawasaki disease may present with hemodynamic instability. An association between viral respiratory infections and Kawasaki disease has been reported. Studies have shown that Kawasaki and Kawasaki-like disease may be associated with and have symptoms overlapping COVID-19. Children with COVID-19 may present as Kawasaki-like disease with pediatric inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Clearly, the blockage of a blood vessel by a microclot is likely to exert pressure on the vessel's walls, potentially weakening it, and so it is reasonable that aneurysms might be expected to accompany diseases involving microclots. This turns out to be the case in rheumatoid arthritis [ 490 ], acute COVID [ 491 , 492 ] (which bears similarities to Kawasaki disease [ 493 ]) and Long COVID [ 17 ]. The association with ME/chronic fatigue syndrome is seemingly weaker, and is usually seen as an association of fatigue, for example, driven by a subarachnoid haemorrhage [ 494 , 495 ].…”
Section: Aneurysmsmentioning
confidence: 99%
“…Clearly, the blockage of a blood vessel by a microclot is likely to exert pressure on the vessel's walls, potentially weakening it, and so it is reasonable that aneurysms might be expected to accompany diseases involving microclots. This turns out to be the case in rheumatoid arthritis [ 490 ], acute COVID [ 491 , 492 ] (which bears similarities to Kawasaki disease [ 493 ]) and Long COVID [ 17 ]. The association with ME/chronic fatigue syndrome is seemingly weaker, and is usually seen as an association of fatigue, for example, driven by a subarachnoid haemorrhage [ 494 , 495 ].…”
Section: Aneurysmsmentioning
confidence: 99%
“…Consequently, researchers have sought to understand the development process of the coronary artery and its influencing factors to intercept or reduce the risk of CAL in KD patients. Some studies have revealed a notable association between low levels of serum 25(OH)D in KD patients with CAL when compared to those without CAL and control groups [ 22 , 27 , 53 ]. Additionally, vitamin D supplementation and adjuvant treatment have been found to effectively mitigate the risk of CAL and improve IVIG treatment response [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…KD can be treated with intravenous immunoglobulin (IVIG), oral aspirin, or anti‐inflammatory agents such as TNF‐α blockers and IL‐1 receptor antagonist 5‐7 . Particularly, early and proper use of IVIG is very important for preventing cardiovascular complications 8 …”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 , 7 Particularly, early and proper use of IVIG is very important for preventing cardiovascular complications. 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation